(untitled) (Global Journal of Computer Science and Technology, 2014)
Banking systems collect huge amounts of data on day to day basis be it customer information transaction details risk profiles credit card details credit limit and collateral details compliance and Anti Money Laundering AML related information trade finance data SWIFT and telex messages Thousands of decisions are taken in a bank daily These decisions include credit decisions default decisions relationship start up investment decisions AML and Illegal financing related One needs to depend on various reports and drill down tools provided by the banking systems to arrive at these critical decisions But this is a manual process and is error prone and time consuming due to large volume of transactional and historical data Interesting patterns and knowledge can be mined from this huge volume of data that in turn can be used for this decision making process This article explores and reviews various data mining techniques that can be applied in banking areas It provides an overview of data mining techniques and procedures It also provides an insight into how these techniques can be used in banking areas to make the decision making process easier and productive